2011
DOI: 10.1097/mpa.0b013e31821bd62f
|View full text |Cite
|
Sign up to set email alerts
|

Cyst Fluid Carcinoembryonic Antigen Is an Accurate Diagnostic Marker of Pancreatic Mucinous Cysts

Abstract: Cyst fluid CEA concentration provides a highly accurate test for the diagnosis of a mucinous cyst, but does not distinguish benign from malignant cysts. Cytology is the most accurate test for the diagnosis of a malignant cyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
206
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(219 citation statements)
references
References 28 publications
7
206
1
3
Order By: Relevance
“…8,11 Studies from our department have indicated that, although CEA analysis is the best test for detecting a mucinous cyst, our data also have revealed that cytologic analysis is the best test for detecting malignancy. 22 Others have demonstrated that detecting atypical cells on cytologic analysis also was the most sensitive test for malignancy compared with imaging studies. 16,17 -in which a ''suspicious'' for malignancy interpretation rather than a ''positive'' cytologic interpretation, as indicated in the 2006 guidelines, is a high-risk feature for malignancy along with an enhancing mural nodule and a dilated main pancreatic duct (!10 mm).…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Studies from our department have indicated that, although CEA analysis is the best test for detecting a mucinous cyst, our data also have revealed that cytologic analysis is the best test for detecting malignancy. 22 Others have demonstrated that detecting atypical cells on cytologic analysis also was the most sensitive test for malignancy compared with imaging studies. 16,17 -in which a ''suspicious'' for malignancy interpretation rather than a ''positive'' cytologic interpretation, as indicated in the 2006 guidelines, is a high-risk feature for malignancy along with an enhancing mural nodule and a dilated main pancreatic duct (!10 mm).…”
Section: Discussionmentioning
confidence: 99%
“…This result is sufficiently powered to demonstrate a significant improvement over cytology ( P =0.002), which has an accuracy of 58% (95% CI: 50%–65%) 7 . The resulting sensitivity is 90% (95% CI: 60–98%) and specificity is 100% (95% CI: 76–100%).…”
Section: Discussionmentioning
confidence: 78%
“…This procedure has an overall sensitivity of less than 50% for detecting malignancy with the majority of results being non-diagnostic 6,7 . During the EUS-FNA procedure the cyst fluid is collected and then analyzed both for tissue (cytopathology) evaluation, and also for the presence of certain molecular markers or glycoproteins, such as carcinoembryonic antigen (CEA).…”
mentioning
confidence: 99%
“…Cytology is the most accurate test for the detection of malignancy in patients with mucinous cysts. 21 A cytological diagnosis of ''positive'' or ''malignant'' is generally 100% specific but very insensitive for detecting highgrade dysplasia. 30,31 Aspirating the contents of the cyst is really a screening test for the detection of dysplastic cells, akin to a Papanicolaou test.…”
Section: Commentary 362mentioning
confidence: 99%
“…Studies have shown that concentrations of around 110 to 200 ng/mL are approximately 80% accurate in determining a cyst to be mucinous. 13,[21][22][23][24][25] Raising the cutoff level improves the specificity of the test but at the expense of sensitivity. 24 Not all mucinous cysts will have such an elevated CEA concentration, and some mucinous cysts have very low concentrations of CEA.…”
Section: Commentary 362mentioning
confidence: 99%